Natural Anti-biofilm Agents: Strategies to Control Biofilm-Forming Pathogens - Mishra, Rojita; Panda, Amrita Kumari; De Mandal, Surajit; Shakeel, Muhammad; Bisht, Satpal Singh; Khan, Junaid (Frontiers in Microbiology, 2020)
Pathogenic microorganisms and their chronic pathogenicity are significant concerns in biomedical research. Biofilm-linked persistent infections are not easy to treat due to resident multidrug-resistant microbes. Low efficiency of various treatments and in-vivo toxicity of available antibiotics drives the researchers towards the discovery of many effective natural anti-biofilm agents. Natural extracts, natural product-based anti-biofilm agents are more efficient than the chemically synthesized counterparts with lesser side effects. The present review primarily focuses on various natural anti-biofilm agents, i.e. phytochemicals, biosurfactants, antimicrobial peptides and microbial enzymes along with their sources, mechanism of action via interfering in the quorum-sensing pathways, disruption of extracellular polymeric substance, adhesion mechanism and their inhibitory concentrations existing in literature so far. This study provides a better understanding that a particular natural anti-biofilm molecule exhibit different mode of actions and biofilm inhibitory activity against more than one pathogenic species. This information can be exploited further to improve the therapeutic strategy by a combination of more than one natural anti-biofilm compounds from diverse sources.